Bacterial 3′UTRs: A Useful Resource in Post-transcriptional Regulation - Menendez-Gil, Pilar; Toledo-Arana, Alejandro (Frontiers in Molecular Biosciences, 2021)
Bacterial prototypical messenger RNAs (mRNAs) is are composed composed of 5' and 3' untranslated regions (UTRs) of athat flank the coding sequences (CDSs) flanked by the 5’ and 3’ untranslated regions (UTRs). In eukaryotes, 3'’UTRs play key roles in post-transcriptional regulatory mechanisms. Shortening or deregulation of these regions is associated with diseases such as cancer and metabolic disorders. Comparatively, little is known about the functions of 3'’UTRs in bacteria. Over the past few years, 3'’UTRs have emerged as important players in the regulation of relevant bacterial processes such as virulence, iron metabolism and biofilm formation. This MicroReview MiniReview is an will update for the different 3'’UTR-mediated mechanisms that regulate gene expression in bacteria. Some of these include 3'’UTRs that interact with their the 5'’UTR counterparts of the same transcript to modulate translation, 3'’UTRs that are targeted by specific ribonucleases, RNA-binding proteins and non-codingsmall RNAs (ncRNAssRNAs), and 3'’UTRs that act as reservoirs of trans-acting ncRNAssRNAs, among others. In addition, recent findings regarding a differential evolution of bacterial 3'’UTRs and its impact in the species-specific expression of orthologous genes are also discussed.